Modelling the triple phase boundary length in infiltrated SOFC electrodes - Vijay, P.; Tade, Moses; Shao, Zongping; Ni, M. (Elsevier Ltd, 2017)
Â© 2017 Hydrogen Energy Publications LLC A model based on the principles of coordination number and percolation theory is proposed for calculating the triple phase boundary (TPB) lengths in the Solid Oxide Fuel Cell (SOFC) electrodes infiltrated with nano particles. The TPB length is a critical microstructural property that influences the cell performance. Empirical expressions for the overall average coordination number and percolation probabilities are proposed to compliment the basic model framework provided by the coordination number principles. The comparison with the numerical and analytical model results from literature is used to both evaluate and interpret the proposed model. The model demonstrates reasonable agreement with literature model and experimental results and provides insights into the coordination number behaviour. This model is a potential alternative to the expensive numerical simulations for the microstructural optimisation of the infiltrated electrodes.